Peran Karang Taruna Bunga Bakung Dalam Pelestarian Hutan Adat Melalui Kearifan Lokal - K. Rapiandi Isak Merang; Iskandar Iskandar (Kaganga:Jurnal Pendidikan Sejarah dan Riset Sosial Humaniora, 2020)
ABSTRACT The purpose of this research is to describe the role and to find out the obstacles of Karang Taruna in Sajau Village in preserving customary forests based on local wisdom. This study used descriptive qualitative method. The results showed that the role of Karang Taruna in the preservation of customary forests in Sajau Village was to collaborate with customary institutions, village government, and the Sajau Village community to monitor, report, and enforce customary law based on local wisdom. Constraints in the preservation of customary forests are due to internal factors of the Sajau Village community taking wood in the customary forest without the permission of the customary institutions and the Sajau Village government and external factors there are people who do not know the boundaries of the customary forest, and the company is interested in buying customary forest land. The conclusions of the research are (1) the role of Karang Taruna in the preservation of customary forests, namely: Coordination with the village government and the Sajau Village customary institution to make and stipulate customary rules, conduct supervision, maintain customary forests, enforce customary law (2) Constraints in the preservation of customary forests, namely: Threats from within the village, communities from outside the village and threats from companies. Keywords: Adat, Forest, Wisdom, Youth Organization.